Al-Kalimāt Dzātu Asl ’Arabiy fī Qāmus As-Sundawi wa Al-Istifādah Minhā fī Ta’līm As-Sundawiyyin - Mada Wijaya Kusumah; Arif Taufikurrahman; Hudaifah (Ukazh: Journal of Arabic Studies, 2021)
هذه اللغة هي لغة القرآن فصارت هذه اللغة محبوبة عندهم ولكنهم يستخدمون بعض اللغة المشهورة فحسب. هؤلاء السندويون أخذوا بعض الكلمات العربية التي لم تكن موجودة عندهم، فكثرت هذه الكلمات ذات أصل عربي في اللغة السندوية ولكن مع ذلك بعضهم لم ينتبهوا على وجود هذه الكلمات بكثرة وجودها في لغتهم اليومية. فقامت الباحثة بهذا البحث بهدف اكتشاف الكلمات السندوية ذات أصل عربي في قاموس اللغة السندوية لرادين ستشاديبراتا من حرف T إلى W، مع معرفة التغيرات الموجودة في اللغة العربية بعد دخولها إلى اللغة السندوية من حيث معنوية ونطقية. إن هذه الدراسة تسلك على منهج الوصفي التحليلي. وقد أثبتت الدراسة وجود الكلمات السندوية ذات أصل عربي في قاموس اللغة السندوية لرادين ستشاديبراتا من حرف T إلى حرف W بلغ 82 كلمة ذات أصل عربي، فقامت الباحثة بتحليلها. فتنقسم هذه الكلمات على أربعة أقسام، فتكون الاستفادة تساعد المعلم على سهولة تعليم اللغة العربية للمبتدئين السندويين بوضع الحوارات والنصوص والتدريبات وألعاب فيها. Arabic is the language of the Qur’an, therefore Arabic is quite familiar ​​among them. However, they only use some popular vocabulary ​​that are not found in the Sundanese language it self. Therefore a lot of Sundanese vocabulary that comes from Arabic origin used by the Sundanese, but most of them do not realize its presence in everyday use. For this reason, this study aims to find Sundanese language vocabulary derived from Arabic found in Sundanese dictionary by Raden Satjadibrata from letter T to W, as well as to know the changes contained in Arabic after entering into the Sundanese, both in terms of their meaning and speech. This research was based on descriptive analysis method and had proven the existence of Sundanese vocabulary derived from Arabic in Sundanese language dictionary written by Raden Satjadibrata, from the letters T to W, which amounts to eighty-two vocabularies, and grouped into four parts. The application of this study can help teachers when teaching Arabic for Sundanese speaking students by placing various discussions, texts, exercises and games of existing vocabulary.